Small Intestinal Bacterial Overgrowth in Type 2 Diabetes Mellitus: Prevalence, Pathophysiology, and Clinical Implications - A Narrative Review - Nowakowski, Michał; Musioł, Aleksandra; Nowakowski, Piotr; Marzec, Jakub; Rakuś, Magdalena; Zagożdżon, Lucyna; Łukasz, Krzysztof; Gwałt, Paweł (Journal of Education, Health and Sport, 2026)
Background. Gastrointestinal symptoms affect up to two-thirds of patients with type 2 diabetes mellitus (T2DM) and are commonly attributed to autonomic neuropathy and dysmotility. Small intestinal bacterial overgrowth (SIBO) has been proposed as a specific small bowel manifestation of diabetic dysbiosis, potentially contributing to worsened glycemic control, impaired beta-cell function, and metabolic-associated fatty liver disease (MAFLD), however, its true prevalence in T2DM and clinical significance remain uncertain. Aim. To synthesize current evidence on the prevalence of SIBO in adults with T2DM, to examine the methodological and clinical factors that influence prevalence estimates, to evaluate proposed pathophysiological mechanisms, and to discuss clinical implications. Material and methods. A selective literature search was conducted in PubMed, Embase, and Web of Science up to March 2026. Observational studies, systematic reviews, meta-analyses, and mechanistic articles reporting SIBO prevalence or associated outcomes in adults with T2DM were included. Results. SIBO is common in T2DM, but prevalence estimates are highly heterogeneous due to differences in diagnostic methods, cut-offs and patient selection. SIBO in T2DM was consistently associated with poorer glycemic control, reduced beta-cell function, autonomic neuropathy, MAFLD, and use of GLP-1 receptor agonists. The distinction between hydrogen-predominant SIBO and IMO, was found to be clinically relevant in T2DM but remained largely underexplored in this population. Conclusions. SIBO affects approximately one in four patients with T2DM when actively investigated, but prevalence estimates vary widely and causal relationships with metabolic outcomes remain unproven. Universal screening is not currently justified; targeted evaluation should be considered in patients with refractory gastrointestinal symptoms, autonomic neuropathy, unexplained deterioration of glycemic control, or MAFLD.